Mt. Etna Feeding System and Sliding Flank: A New 3D Image From Earthquakes Distribution in a Customisable GIS - Guardo, Roberto Antonino (2020)
Fil: Guardo, Roberto. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina